СОДЕРЖАНИЕ ФИНАНСОВОГО ОБЕСПЕЧЕНИЯ ПРОФИЛАКТИЧЕСКОЙ ДЕЯТЕЛЬНОСТИ НАЦИОНАЛЬНОЙ ПОЛИЦИИ УКРАИНЫ - Фелик, Василь Іванович (SUPREMANCE OF LAW, 2017)
The article is devoted to defining the content offinancial provision of the National Preventive Police. The concept offinancial security preventive policing; describes the content offinancial security prevention activities of the National Police; analysis of the structural elements offinancial security and conclusion on the changes that have occurred in this area.
Keywords: National Police; prevention activities; financial support